KEBAHAGIAAN PERNIKAHAN DITINJAU DARI PROBELAMTIKA NUSYUZ PERSPEKTIF SYEH NAWAWI AL-BANTANI - Tsalits Fahami (Conseils : Jurnal Bimbingan dan Konseling Islam, 2023)
Happiness is something that is a goal, a hope that every human being wants to achieve. And when his goals and expectations are achieved, he will feel satisfied, happy and happy. Marriage certainly aims to achieve happiness, because it is impossible for a couple who aims to get married to be unhappy. Then every human being will compete to achieve a happiness, one of which is to get married. Sheikh Nawawi Al-Bantani explained that nusyuz that occurs in the household, the husband should first explain what his wife has done (nusyuz). Explain to the wife about the rights of the wife to the husband and the rights to the wife. The way to deal with it is not arbitrary. Although the study of nusyuz fiqh focuses on the wife's position, it does not rule out the possibility that the husband also performs nusyuz. Marriage will lead to happiness when the couple is able to adapt to a series of household problems that they go through. Nusyuz often occurs due to a lack of communication between husband and wife, so quality communication and a strong marital commitment are needed to be able to enjoy marital happiness.